2014
DOI: 10.4103/0189-6725.143129
|View full text |Cite
|
Sign up to set email alerts
|

An audit of morbidity and mortality associated with foreign body aspiration in children from a tertiary level hospital in Northern India

Abstract: Foreign body aspiration causes considerable morbidity, especially when diagnosis is delayed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 32 publications
(55 reference statements)
2
28
2
Order By: Relevance
“…The mortality rate in this study was 4.7%, which was higher than those in previous reports [22, 23]. Both of these previous reports were from India.…”
Section: Discussioncontrasting
confidence: 71%
“…The mortality rate in this study was 4.7%, which was higher than those in previous reports [22, 23]. Both of these previous reports were from India.…”
Section: Discussioncontrasting
confidence: 71%
“…Foreign body aspiration is a common treatment worldwide for respiratory emergency in children aged between 1 and 3 years and may lead to serious complications . Aspiration of foreign bodies is life‐threatening event without timely and effective diagnosis and treatment . Rigid bronchoscopy under general anesthesia typically is used to remove aspirated foreign bodies, but flexible bronchoscopy under local anesthesia, possibly followed by rigid bronchoscopy, has been used for diagnosis and treatment .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Aspiration of foreign bodies is lifethreatening event without timely and effective diagnosis and treatment. [3][4][5][6][7] Rigid bronchoscopy under general anesthesia typically is used to remove aspirated foreign bodies, 8,9 but flexible bronchoscopy under local anesthesia, possibly followed by rigid bronchoscopy, has been used for diagnosis and treatment. [10][11][12] For example, one group of surgeons performed a retrospective review of 77 children they had treated for airway foreign bodies and reported use of a rigid bronchoscope in 39 cases, use of a flexible bronchoscope in 23 cases, and both in 15 cases.…”
Section: Introductionmentioning
confidence: 99%
“…6,9,10,12 Delayed presentations include unilateral decreased breath sounds, ronchi or crepitations. 13 Persistent cough or non-resolving pneumonia can be one of the delayed signs.…”
Section: Discussionmentioning
confidence: 99%
“…6,8 The complication may include tracheotomy to relieve the upper airway obstruction, or side effects following bronchoscopy or the need for thoracotomy to remove the deepseated foreign body. 13 It was reported that in an Asian study, 5.3% in whom bronchoscopy was performed need to undergo thoracotomy [14][15] . In our series, one patient required tracheostomy for foreign body removal.…”
Section: Discussionmentioning
confidence: 99%